Laparoscopic liver surgery in cirrhosis – Addressing lesions in posterosuperior segments. (March 2019) - Haber, Philipp Konstantin; Wabitsch, Simon; Krenzien, Felix; Benzing, Christian; Andreou, Andreas; Schöning, Wenzel; Öllinger, Robert; Pratschke, Johann; Schmelzle, Moritz
Abstract: Background: Minimal-invasive liver resection has gained considerable attention in recent years, assuming a weighty position in the field of HPB surgery. Even lesions in posterosuperior segments, the technically most challenging localization, have been resected while achieving comparable outcomes to laparotomy. The objective of this study is to evaluate whether the similar beneficial results can be conveyed through minimal-invasive techniques for patients with liver cirrhosis. Materials and methods: We retrospectively analyzed all consecutive patients undergoing laparoscopic liver resection with at least one lesion in the posterosuperior liver segments (IVa, VII, VIII) at our center between January 2012 and July 2018. Patients were separated in two groups based on the presence (n = 43) or absence (n = 115) of liver cirrhosis. Results: Preoperative patient characteristics showed that patients with cirrhosis were older (p < 0.001), had more frequently diabetes (p < 0.005) and a history of alcohol consumption (p < 0.0005). Preoperative liver function, as assessed by LiMAx score was markedly decreased in patients with liver cirrhosis (p < 0.005). While a similar percentage in both groups had anatomical resection, significantly more major resections were performed in patients without cirrhosis (cirrhosis: 23.3% vs. no cirrhosis 55.7%; p < 0.0005). Consequently, surgeries were markedly longer in the no cirrhosis group (p < 0.0005). There was no difference with regard to the need for perioperative transfusion or conversion to laparotomy. There was no differences found between both groups with regard to the postoperative course showing similar ICU- and hospital stays. Complication rate, both with regard to minor and major complications, as well as rate of clear resection margins were similar between the two groups as well. Conclusion: Patients with liver cirrhosis and a lesion in the posterosuperior liver segments are amenable to the minimal-invasive approaches as no significant differences can be observed with regard to safety and oncologic sufficiency. As these procedures are from a technical perspective challenging, they should be performed in specialized centers.